Testing JavaScript Applications - Da Costa, Lucas (Manning Publications, 2021)
Testing JavaScript Applications teaches you how to implement an automated testing plan for JavaScript-based web applications. It describes practical testing strategies, covers useful tools and libraries, and explains how to foster a culture of quality. In this clearly-written, example-rich book, you'll explore approaches for both backend and frontend applications and learn how to validate your software much more quickly and reliably.